Synthesis of 6H-Isoindolo[2,1-a]indol-6-ones via Palladium-Catalyzed Carbonylative Cyclization of 2-(2-Bromophenyl)-1H-indoles - Yoo, Jae Myeong; Ho, Son Long; Cho, Chan Sik (Synlett, 2016)
2-(2-Bromophenyl)-1H-indoles are carbonylatively cyclized under carbon monoxide pressure in toluene in the presence of a catalytic amount of PdCl2 and PPh3 along with a base to give 6H-isoindolo[2,1-a]indol-6-ones in high yields.
Keywords: carbonylation; cyclization; heterocycles; indolones; catalysis